Escape from a disk with partly absorbing boundaries driven by bi-variate α-stable noises. (20th May 2016) - Szczepaniec, Krzysztof; Dybiec, Bartłomiej
Abstract: In this paper we explore the problem of first escape from the disk. The part of the disk edge, i.e. the arc controlled by the angle ϕ, is absorbing. For an appropriate choice of parameters the mean first passage time (MFPT) is a non-monotonous function of the stability index α describing jumps' length asymptotics. The dependence of the MFPT on the stability index α is sensitive to the way in which the non-absorbing part of the disk edge is accounted for.